Proceedings of the Thirty-Eighth Annual ACM Symposium on Theory of Computing 2006
DOI: 10.1145/1132516.1132594
|View full text |Cite
|
Sign up to set email alerts
|

Integrality gaps for sparsest cut and minimum linear arrangement problems

Abstract: Arora, Rao and Vazirani [2] showed that the standard semidefinite programming (SDP) relaxation of the Sparsest Cut problem with the triangle inequality constraints has an integrality gap of O( √ log n). They conjectured that the gap is bounded from above by a constant. In this paper, we disprove this conjecture (referred to as the ARV-Conjecture) by constructing an Ω(log log n) integrality gap instance. Khot and Vishnoi [16] had earlier disproved the non-uniform version of the ARV-Conjecture.A simple "stretchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(79 citation statements)
references
References 28 publications
1
78
0
Order By: Relevance
“…This has been a rather unique approach to the construction of counterexamples in metric geometry. The lower bound was improved to Ω(log log n) by Krauthgamer and Rabani [27], and shortly afterward Devanur, Khot, Saket, and Vishnoi [18] showed that even the Sparsest Cut relaxation has an integrality gap Ω(log log n).…”
Section: Semidefinite Programming and Uniquementioning
confidence: 99%
“…This has been a rather unique approach to the construction of counterexamples in metric geometry. The lower bound was improved to Ω(log log n) by Krauthgamer and Rabani [27], and shortly afterward Devanur, Khot, Saket, and Vishnoi [18] showed that even the Sparsest Cut relaxation has an integrality gap Ω(log log n).…”
Section: Semidefinite Programming and Uniquementioning
confidence: 99%
“…This improves over the O(log n)-approximation of Rao and Richa. These SDP relaxations were shown to have integrality gap Ω(log log n) by Devanur, Khot, Saket & Vishnoi [10]. As noted in [10], it remains a challenging open problem to prove a hardness of approximation result for Sparsest Cut and OLA.…”
Section: Introductionmentioning
confidence: 99%
“…These SDP relaxations were shown to have integrality gap Ω(log log n) by Devanur, Khot, Saket & Vishnoi [10]. As noted in [10], it remains a challenging open problem to prove a hardness of approximation result for Sparsest Cut and OLA. The currently known hardness results apply only 1 Also known as Minimum Linear Arrangement.…”
Section: Introductionmentioning
confidence: 99%
“…These connections are further explained in Section 8.2. The KKL Theorem has been used to prove a super-constant inapproximability result for the non-uniform Sparsest Cut problem by Chawla et al [25] and to construct Ω(log log N ) integrality gaps for a natural SDP relaxation for the non-uniform as well as the uniform Sparsest Cut problem [75,33], improving on the integrality gap obtained earlier in [71].…”
Section: Bourgain's Noise-sensitivity Theoremmentioning
confidence: 99%